Pectin and pectinases: Production, characterization and industrial application of microbial pectinolytic enzymes - Pedrolli, Danielle Biscaro [UNESP]; Monteiro, Alexandre Costa [UNESP]; Gomes, Eleni [UNESP]; Carmona, Eleonora Cano [UNESP] (Bentham Science Publishers, 2009)
Pectinases are a big group of enzymes that break down pectic polysaccharides of plant tissues into simpler molecules like galacturonic acids. It has long been used to increase yields and clarity of fruit juices. Since pectic substances are a very complex macromolecule group, various pectinolytic enzymes are required to degrade it completely. These enzymes present differences in their cleavage mode and specificity being basically classified into two main groups that act on pectin smooth regions or on pectin hairy regions. Pectinases are one of the most widely distributed enzymes in bacteria, fungi and plants. This review describes the pectinolytic enzymes and their substrates, the microbial pectinase production and characterization, and the industrial application of these enzymes. © Pedrolli et al.; Licensee Bentham Open.
Keywords: Pectin; Pectinase; Pectinolytic; Break down; Galacturonic acids; Main group; Pectic polysaccharides; Pectinases; Pectinolytic enzyme; Plant tissues; Biopolymers; Catalysts; Enzymes; Fruit juices; Industrial applications; Polysaccharides; Biochemical engineering; pectate lyase; pectin; pectin acetylesterase; pectin lyase; pectinesterase; polygalacturonase; polymethylgalacturonase; rhamnogalacturonan acetylesterase; rhamnogalacturonan hydrolase; rhamnogalacturonan lyase; rhamnogalacturonan rhamnohydrolase; rhamnogalcturonan galacturonohydrolase; unclassified drug; xylogalacturonan hydrolase; enzyme activity; enzyme analysis; enzyme degradation; enzyme localization; enzyme purification; enzyme specificity; enzyme structure; enzyme synthesis; nonhuman; pH measurement; priority journal; protein cleavage; review; temperature measurement; Fungi